LiF@PFSA-Based Composite Membranes for PEM Fuel Cells at Intermediate Temperature Conditions - Kutter, Maximilian; Hilgert, Annika; Maier, Maximilian; Schilling, Monja; Greve, Christopher R.; Loukrakpam, Rameshwori; Hagemeier, Wiebke; Rosin, Andreas; Muggli, Mark; Herzig, Eva M.; Zeis, Roswitha; Böhm, Thomas; et al. (ACS Applied Polymer Materials, 2025)
Polymer electrolyte membrane fuel cells (PEMFCs) operating at temperatures above 100 °C offer an interesting opportunity for heavy-duty applications. Especially for intermediate operating temperatures between 110 and 130 °C (IT-PEMFC), faster reaction kinetics, higher tolerance to fuel impurities, and water flooding as well as improved heat management of the fuel cell system have been observed. Perfluorosulfonic acid-based membranes (PFSAs) can be modified by incorporating additives or (nano)particle filler systems to improve their thermal and mechanical stability, proton conductivity, and long-term performance at these increased temperatures. Here, we investigate the effect of lithium fluoride particles embedded in PFSA membranes on their water retention behavior as well as on membrane durability in single-cell tests at elevated PEMFC operating temperatures of up to 120 °C. The lithium fluoride nanoparticle-modified membrane shows increased cell performance under both standard and intermediate temperature conditions. The observed performance boost can be explained by an increased mechanical stability at elevated temperatures of the membrane, due to stabilizing hydrophobic and hydrophilic domains, and an increased water uptake and storage capability, especially at low humidity levels during full cell operation. We propose that the nanoparticles adsorb water molecules by hydrogen bond formation, thus enhancing proton conductivity even at high temperatures resulting in these increased full cell performances of the LiF@PFSA-based composite membrane.
CRIS-Team Scopus Importer:2025-02-14
Keywords: composite membranes; in situ Raman; intermediate temperature PEM fuel cells; metal fluorides; SAXS study; water retention